2016
DOI: 10.1007/s00374-016-1103-y
|View full text |Cite
|
Sign up to set email alerts
|

Does acidification of a soil biofilter compromise its methane-oxidising capacity?

Abstract: A biofilter made using volcanic pumice soil from a landfill in Taupo, New Zealand has been found to mitigate CH 4 emissions from New Zealand dairy effluent ponds. However, the biofilter after drying out following almost 5 years of use removed little or no CH 4 . Furthermore, H 2 S present in the biogas (from the dairy effluent ponds) had increased the acidity (pH) in the soil biofilter from 5.2 to 3.72 during this 5-year period. In this study, we adjusted the soil moisture to 60 % water-holding capacity (WHC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
2
8
1
Order By: Relevance
“…Interestingly, an increasing trend in the abundance of the Methylocapsa ‐like methanotrophs was noticed in the pond biofilters, and this could be related to the ability of these methanotrophs to grow under acidic conditions. This concurs with our previous research finding (Syed et al, 2016b). Although the diversity (Shannon's) increased in the pond biofilters over the study period, the population remained even, which suggested the presence of a stable methanotroph community in the pond biofilters.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Interestingly, an increasing trend in the abundance of the Methylocapsa ‐like methanotrophs was noticed in the pond biofilters, and this could be related to the ability of these methanotrophs to grow under acidic conditions. This concurs with our previous research finding (Syed et al, 2016b). Although the diversity (Shannon's) increased in the pond biofilters over the study period, the population remained even, which suggested the presence of a stable methanotroph community in the pond biofilters.…”
Section: Discussionsupporting
confidence: 94%
“…The increase in type I methanotroph abundance was supported by the increase in the Methylobacter group of methanotrophs, but the Methylococcus abundance was very low. The suppressed growth of the Methylococcus population at higher CH 4 concentrations was also evident in our previous studies (Syed et al, 2016a, 2016b). Interestingly, an increasing trend in the abundance of the Methylocapsa ‐like methanotrophs was noticed in the pond biofilters, and this could be related to the ability of these methanotrophs to grow under acidic conditions.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations